2006
DOI: 10.1021/ac060851a
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Gas Chromatographic Separation of Organophosphor and Organosulfur Compounds Utilizing a Microcountercurrent Flame Photometric Detector

Abstract: A microcountercurrent flame photometric detector (microcc-FPD) was adapted and optimized for ultrafast gas chromatographic (GC) separation and detection of organophosphor (OP) and organosulfur (OS) compounds on short chromatographic columns. Air and hydrogen are introduced to the microcc-FPD from opposite directions, creating a hydrogen-rich flame. In this microcc-FPD, combustion takes place between the burner tips without touching them. The separation between the tips and the flame reduces heat loss from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…Usually, GC [9] and HPLC [10] are coupled to an element specific detector (FPD) [11][12][13] or to a mass spectrometer (MS) [14][15][16] because these detection techniques provide very reliable identification of separated compounds. Each of these techniques has advantages and drawbacks for on-site analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Usually, GC [9] and HPLC [10] are coupled to an element specific detector (FPD) [11][12][13] or to a mass spectrometer (MS) [14][15][16] because these detection techniques provide very reliable identification of separated compounds. Each of these techniques has advantages and drawbacks for on-site analysis.…”
Section: Introductionmentioning
confidence: 99%
“…The capability of fast GC together with transportable GC/MS for fast analysis has been well demonstrated by Mustacich (37) and Contreras et al (38) An ultrafast GC analysis of dimethyl methylphosphonate and diisopropyl methylphosphonate was achieved within <5 s using very fast temperature programming and a 0.5-m-long microbore column. (39) Comprehensive GC (GC × GC) is based on continuous collection of the effluent from the GC column and periodic reinjection of a small portion of the effluent to a second column of different properties. (40) The major advantage of this technique is improved separation power and it has been successfully used for the analysis of CWC-related chemicals in complex sample matrices.…”
Section: Columnsmentioning
confidence: 99%
“…Kendler et al. demonstrated that GC separation of a group of organophosphor compounds and benzothiophene was achieved by a micro chromatographic column coated with 200–300 nm thick dimethyl polysiloxane (100%) using a microcountercurrent flame photometric detector. Also, Radadia et al.…”
Section: Introductionmentioning
confidence: 99%
“…The microfabricated column with embedded microposts was described by Sun [12] which can be effectively used in the field of environmental monitoring. Kendler et al [13] demonstrated that GC separation of a group of organophosphor compounds and benzothiophene was achieved by a micro chromatographic column coated with 200-300 nm thick dimethyl polysiloxane (100%) using a microcountercurrent flame photometric detector. Also, Radadia et al utilized a 100 μm wide and 3 m long serpentine micromachined channel filled with the mixture of methyl (95%) + phenyl (5%) polysiloxanes and dicumyl peroxide as stationary phase for the separation of organophosphonate and organosulfur compounds (isopropyl sulfide, chloroethyl methyl sulfide, and isopropyl sulfonyl chloride) utilizing a microcountercurrent flame photometric detector [14].…”
Section: Introductionmentioning
confidence: 99%